A novel biochemical marker for community-acquired pneumonia: Ischemia-modified albumin - Bolatkale, Mustafa; Düger, Mustafa; Ülfer, Gözde; Can, Çağdaş; Acara, Ahmet Çağdaş; Yiğitbaşı, Türkan; Seyhan, Ekrem Cengiz; Bulut, Mehtap (W.B. Saunders, 2017)
Introduction Community-acquired pneumonia (CAP) is a frequent cause of hospitalization and a leading cause of mortality worldwide. Early diagnosis and the initiation of appropriate antibiotic therapy are essential to reduce pneumonia-related morbidity and mortality. CRP is a well-established biomarker in many clinical settings, but has been traditionally considered not specific enough to be a useful guide in the diagnostic process of pneumonia. There is still a need for more specific and practical markers in CAP for diagnosis. The aim of this study was to investigate the diagnostic value of ischemia-modified albumin (IMA) levels in the diagnosis of CAP in the Emergency Department. Methods The study included 81 patients admitted with CAP and 81 control patients. Initial hour levels of IMA and CRP were measured. The IMA mean levels were compared between the study and control group. Correlation analyses were performed to investigate the association of serum IMA levels with CRP. Results Mean levels of IMA were 0.532 ± 0.117 IU/ml in the study group and 0.345 ± 0.082 IU/ml in the control group. IMA levels were significantly higher in the study group compared to the control group. The IMA level of 0.442 IU/ml had sensitivity of 75.3% and specificity of 91.3% and was positively correlated with CRP levels (r = 0.506; p < 0.05). Conclusion Blood IMA levels significantly increase in adult patients presenting with CAP. IMA may be considered as a novel biomarker in the diagnosis of CAP.
Keywords: C-Reactive Protein; Community Acquired Pneumonia; Ischemia Modified Albumin